Analysis of students spatial ability in solving problems of flat side space subjects based on van hieles level of thinking - Iqra Matul Aulia; Sudi Prayitno; Ulfa Lu luilmaknun; Nyoman Sridana (Department of Mathematics and Science Education, Faculty of Teacher Training and Education, University of Mataram. Jurnal Pijar MIPA colaborates with Perkumpulan Pendidik IPA Indonesia Wilayah Nusa Tenggara Barat, 2023)
This study aims to describe students' spatial abilities in solving geometrical problems of flat-sided shapes based on van Hiele's level of thinking in grade eight junior high school of SMP Negeri 1 Aikmel in the academic year 2020/2021. This type of research is descriptive qualitative. The research subjects were taken by purposive sampling, namely nine students of class VIII consisting of 3 students, each with van Hiele thinking level 0 (visualization), level 1 (analysis), and level 2 (abstraction). Subjects were selected based on having received material on plane shapes and had taken the van Hiele geometry test. Data collection techniques were van Hiele's geometry ability test, spatial ability test, and interviews. Data validity uses Aiken and triangulation methods. The results of this study indicate that: (1) subjects with level 2 (abstraction) have spatial abilities consisting of visualization, spatial orientation, and spatial rotation. (2) subjects with level 1 (analysis) have spatial abilities consisting of spatial orientation. (3) subjects with level 0 (visualization) do not have spatial abilities.